Practices of climate responsibility - Moos, Thorsten; Arndt, Megan (npj climate action, 2023)
In the context of climate protection, the notion of responsibility is regularly invoked to address individuals and collectives as liable to urgent climate action. The article argues for an understanding of responsibility not only as a normative (and counterfactual) concept but also as a social practice. As an analytical tool to examine the complex social reality of responsibility, the concept of responsibility practices is introduced. Following four constitutive dimensions of responsibility, this approach allows for studying how responsibility is negotiated between individual and collective subjects, how the scope of responsibility is adjusted between local and global foci, what values (e.g., economical, political, and moral norms) are invoked, and towards which internal, external or virtual authorities responsibility is addressed. As an example, carbon offsetting programs are analyzed as bundles of practices of attributing, negotiating, and refusing responsibility. This praxeological account is useful to complement psychological and behavioral economy approaches to the knowledge-action gap. Especially, it facilitates the empirical consideration of denying, avoiding, and delegating responsibility. It can be expected that research on responsibility practices will contribute to a more realistic concept of climate responsibility.
Gesehen am 16.11.2023